2023
DOI: 10.1101/2023.02.27.530174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine dysregulation in Parkinson’s disease flattens the pleasurable urge to move to musical rhythms

Abstract: The pleasurable urge to move to music (PLUMM) elicits activity in motor and reward areas of the brain and is thought to be driven by predictive processes. Dopamine within motor and limbic cortico-striatal networks is implicated in the predictive processes underlying beat-based timing and music-induced pleasure, respectively. This suggests a central role of cortico-striatal dopamine in in PLUMM. This study tested this hypothesis by comparing PLUMM in Parkinson's disease patients, healthy age-matched, and young … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…Group synchrony in music is more likely a manifestation of adaptations related to bonding and cooperation that produce effects in numerous behavioral domains—after all, we synchronize in many activities, and not always rhythmically 122 . Many of music's pleasurable effects do not require participation in collective behavior to be experienced 123,124 . Furthermore, the pleasurable effects of musical synchrony 125 can also be produced from asynchronous activities, 126 and may be occasioned by group membership itself rather than specific activities the group might engage in 127 .…”
Section: Discussionmentioning
confidence: 99%
“…Group synchrony in music is more likely a manifestation of adaptations related to bonding and cooperation that produce effects in numerous behavioral domains—after all, we synchronize in many activities, and not always rhythmically 122 . Many of music's pleasurable effects do not require participation in collective behavior to be experienced 123,124 . Furthermore, the pleasurable effects of musical synchrony 125 can also be produced from asynchronous activities, 126 and may be occasioned by group membership itself rather than specific activities the group might engage in 127 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the present stimuli added reverberation in their reconstructions of the expert drum patterns, which increased acoustic liveness of the percept, and thus the perceived ecological validity of the experiment for the listener. While researcher-composed stimuli are effective in establishing the landmark findings that relate the scientifically generalizable concept of syncopation and rhythmic complexity to the pleasurable urge to move, stimuli that are more ecologically valid and that maximize the enjoyment of the listener may be effective at bridging the gap between lab-based research and real-world applications [ 48 ], such as the design and implementation of music-based interventions that tap into pleasure and movement mechanisms for movement disorders such as Parkinson’s Disease [ 3 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, dopamine dysregulation in patients with Parkinson's Disease (PD) was found to be associated with flatten responses to musical groove (i.e., the pleasurable urge to move to musical rhythms) (Pando-Naude et al, 2023). Specifically, older adults in this study showed less preference and sensitivity to the complexity of musical rhythms, suggesting a reduced ability to register and process the precision of sensory evidence, amidst biases for top-down consolidated prior models and preferences acquired through lifelong musical experiences.…”
Section: Shift In Precision Of Sensory Learning With Age: Evidence Fr...mentioning
confidence: 99%
“…Another important form of intervention for older adults is motor rehabilitation, which either aims to restore motor deficits as a result of neurodegenerative diseases, or to combat increasing prevalence of falls in this age group. The underlying mechanisms for attaining benefits in the motor domain are suggested to be multifactorial (Thaut, 2003), including but not limited to the activation of the dopaminergic system as a result of movement and pleasurable feelings elicited by music (Ferreri, Mas-Herrero, et al, 2019, albeit a reduced intensity in PD -see Pando-Naude et al, 2023), and endogenous mechanisms that help maintain the effect of entrainment when external pacing cues cease (Rose et al, 2019), and rhythmic entrainment mediated by auditory-motor coupling.…”
Section: Effects Of Rhythmic Entrainment On Motor Rehabilitationmentioning
confidence: 99%